Same patient but different worlds: A state-of-the-art review translating best practice psychosocial care from musculoskeletal care to the orthopaedic context - Marie K. March; Katharine E. Roberts (BMC Musculoskeletal Disorders)
Abstract Background Individuals with chronic musculoskeletal conditions experience persistent pain and disability that has deleterious impacts on physical function, psychological health, social engagement, relationships, and work participation. This impact is greater in people with psychosocial risk factors, and best practice musculoskeletal care recommends a biopsychosocial approach to management. Orthopaedic surgery is often an effective management approach for chronic musculoskeletal conditions, but research has only recently explored the links between differing patient outcomes after orthopaedic surgery and psychosocial risk factors. Implementing biopsychosocial approaches to musculoskeletal care has taken great strides in the primary care setting however, implementation of the biopsychosocial approach in orthopaedic surgery brings complexity as the context changes from primary care to hospital based secondary care. The aim of this review therefore is to explore implementation of psychosocial care in the elective orthopaedic surgery context, informed by evidence in musculoskeletal care. Assessment and management of psychosocial factors Several composite screening tools for psychosocial factors or ‘yellow flags’ are recommended for use in primary care for musculoskeletal conditions alongside a comprehensive patient interview. However, in the orthopaedic surgery context, composite measures have focused on discharge destination, and there is not a universal approach to comprehensive patient interview incorporating a biopsychosocial approach. A range of biopsychosocial approaches to musculoskeletal conditions have been developed for the primary care setting, yet few have been explored in the context of orthopaedic surgery. Implementation of psychosocial care Implementing best practice psychosocial care into the orthopaedic context has enormous potential for all stakeholders, but several barriers exist at the level of the individual patient and practitioner, workforce, health service and society. We have discussed key considerations for implementation including workforce composition, patient-centred care and shared decision making, health literacy, continuity of care, and consideration of preferences for women and culturally diverse communities. Conclusion This review considers current literature exploring implementation of psychosocial care into the orthopaedic surgery context, informed by current research in musculoskeletal care. This presents a critical opportunity for orthopaedic surgery to provide optimised, equitable, high-value, patient-centred care.